Nanosynthesis, and structural and dosimetric characteristics of undoped and copper manganese-doped calcium borate thermoluminescent dosimeters - Haghiri, Maryam Erfani (2013)
Tissue equivalent thermoluminescent dosimeters (TLDs) are an effective device to measure low and high absorbed doses of ionizing radiation in protected area, medical and industrial applications or as a personal monitoring dosimeter. A number of commercially available TLDs are common for this purpose where the TL intensity is proportional to absorbed dose but they are of a narrow dose range. In this research efforts were made to enhance the present TL performance of these materials to a wider dose range by employment of nanosynthesis method and introducing impurities to the TL materials. The un-doped and Cu-Mn doped calcium tetraborate nanocrystals (CaB4O7) were fabricated using the combination of co-precipitation and heat-treatment methods. For the un-doped samples, 100 ml de-ionized water containing 0.2-mol calcium chloride (CaCl2), 0.5-3 wt% of Polyvinyl pyrrolidone (PVP) were mixed with 100 ml de-ionized water containing 0.2-mol borax (Na2B4O7) drop wise to form fine white precipitations of calcium tetraborate (CaB4O7). For the doped samples, manganese chloride (MnCl2) and copper chloride (CuCl2) were added into the PVP solution before mixing with borax. The precipitations were then centrifuged (3500 rpm for 10 min) and washed several times with distill water before drying at 80 oC for 24 h and annealing at temperatures between 700 to 970 oC and at fixed annealing times of 1 to 5 h. The synthesized un-doped and Cu-Mn doped CaB4O7 nanocrystals were used to investigate the structural and thermoluminescent characteristics. The XRD patterns of synthesized nanparticles at initial precipitation showed almost crystalline structure as compared to those undergone thermal treatment at the annealing temperatures of 750 to 900 oC where the dominant phase structure became ortothrombic structure. Increasing annealing temperature from 700 to 970 oC, the aggregation of the nanoparticles enlarged and the average particle size increased from 5.5 to 14 nm as measured by the transmission electron microscopy (TEM). The extension of annealing time did not show a significant change in the conversion of phase structure except small variation in the peak positions. The mono-dispersed and spherical shape calcium borate nanoparticles were realized using 1-wt% PVP stabilizer to produce the average particle sizes of 5.5 nm at the initial precipitation and 8 nm at the optimum annealing temperature of 970 oC for 1 hour annealing time. The manganese doped calcium borate (CaB4O7:Mn) nanocrystals showed a single TL peak at around 149 oC with enhanced TL sensitivity over the un-doped CaB4O7 nanocrystals by 60 times and produced a good linearity response from 0.05 to 2000 Gy. However, it showed high degree of fading of 52 % per month and failed to become a good TLD phosphor. The copper doped calcium borate (CaB4O7:Cu) nanocrystals showed two prominent TL peaks located at 114 and 246 oC. The TL sensitivity of low and high temperature peaks of (CaB4O7:Cu) nanocrystals increased by 1 and 3 times compared to un-doped samples, respectively. The remarkable feature of this nanophosphor is on its wide range linear dose response from 0.05 to 3000 Gy for the high temperature peak of 246 oC and its limited range linear dose response from 0.05 to 30 Gy for the low temperature peak of 114 oC. The fading was 26 % in 2 months storaged in a dark room for the high temperature peak and a poor fading for the low temperature peak after 1 week. The TL response of double doped calcium borate (CaBT:Cu-Mn) nanocrystal showed two prominent TL peaks located at 124 and 256 oC. The incorporation of manganese into the host lattice, as a co-dopant, increased the TL efficiency of low and high temperature peaks by 2.30 and 3.67 times more than un-doped samples, respectively. The double doped nanophosphor revealed an excellent linearity dose respond in the range of 0.05 to 3000 Gy for both temperature peaks. The low temperature peak displayed a considerable fading after 1 week storage, whilst the high temperature peak presented the fading of 23 % after 2 month storage in a dark room. As a comparative study, the TL sensitivity of single and double doped calcium borate nanocrystals were compared with the one of the standard and commercial TL dosimeter, TLD 100 (LiF:Mg,Ti) after exposure to 10 Gy gamma dose. The results demonstrated that the manganese (1.4 mol%) doped calcium borate nanocrystal has a sensitivity of 2.75 times higher than the TLD100. However, the sensitivity of copper doped and copper-manganese CaBT nanocrystals at this particular exposure (i.e. 10 Gy) is less than that of TLD-100 phosphor by a factor of approximately 0.04 and 0.09 times for low temperature peak and 0.13 and 0.14 for high temperature peak, respectively.